Application of acidic electrolyzed water combined with packaging to maintain quality and storage life of fresh-cut ‘Phulae’ pineapple - Raiputta J. (2017)
© 2017, International Society for Horticultural Science. All rights reserved. ‘Phulae’ pineapple (Ananas comosus (L.) Merr.) is one of Geographical Indications of Chiang Rai Province, Thailand. It is a good source of soluble dietary fiber, beta carotene and bromelain. The demand of fresh-cut ‘Phulae’ pineapple becomes increasing due to its small size and difficulty in peeling. Therefore this work aims to study the effect of acidic electrolyzed water (AEW) combined with packaging on quality and prolonging storage life of fresh-cut ‘Phulae’ pineapple. Treatment of AEW at 80 mg L-1 available chlorine for 2 min was selected to combine with 4 types of packaging: polypropylene (PP) bag, PP-antifog (PP-AF) bag, PP-AF film and M-wrap. Non-treated samples were controls. Quality in terms of pH, total soluble solids (TSS), titratable acidity (TA), vitamin C content, color, firmness, juice leakage (JL), total plate count (TPC), coliform, yeast and mold and sensory evaluation were determined during 0-14 days of storage at 5±1°C, 95% RH. The pH, TSS and TA values did not significantly change over the time of storage (P > 0.05). Treated samples packed in PP-AF bag (oxygen transmission rate (OTR): 3,685 mL m -2 d -1 ) obtained the highest vitamin C content as 17.03 mg 100 g -1 fresh weight at 14 days storage. Juice leakage was observed after 2 days storage in all treatments. Moreover, TPC and yeast and mold in treated samples packed in PP-AF bag were lower than other treatments (4.13 log colony forming unit (CFU) g -1 and 1.3×10 3 CFU g -1 , respectively). The combination of AEW and PP-AF bag increased the storage life from 10 days to about 14 days at 5±1°C, 95% RH.